Marine Biological Reference Collections: CBMR-General (ICM-CSIC) - Santos, Ricardo; Sabatés, Ana; Ramón, Montserrat; Villanueva, Roger; Lombarte, Antoni; Abelló, Pere; Guerrero, Elena (2023)
The Marine Biological Reference Collections (CBMR) are located at the Institute of Marine Sciences (ICM-CSIC) in Barcelona, Spain. The CBR are a Unit of Service where around 15000 referenced species are preserved, catalogued and maintained for their study. The most represented marine groups at the CBMR are fish, crustaceans, molluscs and echinoderms, but also other groups are present. The studies based on the CBMR specimens are focused on biodiversity, biogeography, taxonomy (type species), invasive and alien species, and genetic analysis. Several PhD theses have also been carried out in collaboration with the CBMR.The CBMR are a reference point for the marine biodiversity of the Mediterranean Sea, but in their facilities the CBMR also hold specimens from all the oceans (Atlantic, Pacific, Indian, Antarctic and Arctic). The Collections are constantly receiving new specimens and updating. The main sources of specimens are oceanographic surveys and different kind of sampling programs carried out by the research projects run by the ICM-CSIC. However, the CBMR have also received (in the past and currently) different collections donated by naturalists, researchers, other institutions, and particulars. The CBMR were created in 1981, in the earlier history of the ICM-CSIC, by Jaume Rucabado, Domingo Lloris and Concepción Allué. The Collections were later recognized and catalogued by the Spanish Ministry of Culture in 1990. In the last decade, the CBMR initiated a new stage where the information was digitized and the physical preservation of specimens updated to the new rules (such as change from formaldehyde to ethanol). The CBMR are now part of GBIF (Global Biodiversity Information Facility), thus making public and available all data collections and their metadata. We have also incorporated the use of Geographical Information Systems (GIS) to monitor and study the geographical distribution of our specimens and moreover, the CBMR started to act as repository of DNA voucher collections for genetic analyses.As a unit of ...